PEDAGOGICAL APPROACH TO ENGLISH GRAMMAR STRUCTURES: THE CASE OF EFAL TEACHERS IN SELECTED SCHOOLS IN LIMPOPO PROVINCE, SOUTH AFRICA - Montle, Malesela Edward; Mashiane, Mmetlane Valery; Kekana, Tebogo Johannes (Universitas Islam Sumatera Utara (UISU), 2025)
English grammar instruction is fundamental to learners’ success, especially in contexts where English is not a first language. However, despite its importance, the teaching and learning of English grammar continue to face persistent challenges. This paper investigates the teaching of English First Additional Language (EFAL) grammatical structures in selected public secondary schools in Limpopo Province, South Africa, and identifies obstacles to effective grammar instruction. The study was prompted by learners’ inadequate grammatical proficiency, as reflected in National Senior Certificate (NSC) examination results. Employing a qualitative exploratory design, data were collected through classroom observations of Grade 11 EFAL teachers across five schools representing five education districts. The study is grounded in both the Grammar Translation and Communicative Language Teaching approaches. Its significance lies in exploring the practical realities of grammar instruction, thereby shedding light on possible causes of learners’ grammatical weaknesses. Findings reveal that while some teachers demonstrated a sound understanding of grammar rules and structures, others showed misconceptions regarding grammar teaching. Evidence of learner interlanguage, permeability, and fossilization was also observed. Moreover, teachers employed varying degrees of adaptation of the three approaches and utilized diverse teaching and learning materials. The study concludes that effective grammar instruction requires enhanced teacher training in the integration of multiple pedagogical approaches to strengthen learners’ understanding of English grammatical structures.